Digital Marketing and Halal Certification: An Integrated Approach to Increasing the Competitiveness of Bandung's MSMEs - Meirani Rahayu Rukmanda; Bambang Heryanto; Supandi; Nurhadi; Arjun Ahmad Firdaus (Journal of Islamic Economics and Business, 2025)
The Micro, Small, and Medium Enterprises (MSMEs) sector in Bandung City faces significant challenges in integrating Digital Marketing and Halal Certification (SH) amidst regional diversity. This study aims to identify supporting factors, analyze emerging substantive obstacles, and formulate potential optimizations for integrating these two aspects to improve MSME competitiveness. This study adopted a qualitative approach with a case study design, involving 50 MSMEs selected by purposive sampling from five main areas of Bandung City. Data were collected through semi-structured interviews, observation, and documentation, with validity guaranteed through triangulation procedures. A substantial digital and bureaucratic disparity gap was found between central and peripheral MSMEs. Central MSMEs gain a competitive advantage from the digitalization of halal licensing supported by mentoring, while peripheral MSMEs are hampered by minimal literacy and regulatory complexity. The synergy between digital promotion and halal labels empirically increases turnover and consumer loyalty, where Halal Certification functions as a trust heuristic validated in real time on online platforms. The main conclusion is the need to implement an Integrated Halal Digital Infrastructure Model. This model simultaneously synchronizes the MSME digitalization process with the halal audit stages, effectively reducing the gap and making halal compliance an accelerator for a competitive digital market.